Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 2 - Section 2.3 - Further Solving Linear Equations - Exercise Set: 44

Answer

x = -11

Work Step by Step

$\frac{5(x - 1)}{4} = \frac{3(x + 1)}{2}$ Distribute: $\frac{5x - 5}{4} = \frac{3x + 3}{2}$ Multiply both sides by the Least Common Denominator, 4: $4(\frac{5x - 5}{4}) = 4(\frac{3x + 3}{2})$ 5x - 5 = 2(3x + 3) 5x - 5 = 6x + 6 Subtract 5x from both sides: -5 = x + 6 Subtract 6 from both sides: -11 = x x = -11
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.